Respostas
respondido por:
77
Primeiro vamos tentar isolar w na equação
3w+2u=1/2v+w
3w - w=1/2v - 2u
2w = 1/2v - 2u
w = 1/2 (1/2v - 2u)
w = 1/4.v - u
w = 1/4(-2,4) - (3, -1)
w = (-1/2, 1) - (3, -1)
w = (-1/2 - 3, 1 + 1)
w = (-7/2, 2)
3w+2u=1/2v+w
3w - w=1/2v - 2u
2w = 1/2v - 2u
w = 1/2 (1/2v - 2u)
w = 1/4.v - u
w = 1/4(-2,4) - (3, -1)
w = (-1/2, 1) - (3, -1)
w = (-1/2 - 3, 1 + 1)
w = (-7/2, 2)
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás